Thinking better A revoulutionary new program to achieve peak mental performance - Lewis, David frey50 (Rawson, Wade New York, 1982)
"Thinking Better" is based on the concept that we can enhance our intellectual performance to an astounding degree by applying the strengths of state-of-the-art computer science - speed, efficiency, precision, razor-sharp logic that misses nothing.
Keywords: Problem solving; Greene, James -- Succes